The Effect of News Peril-type on Social Inclinations: A Social Group Comparison. (September 2020) - Riles, Julius Matthew; Behm-Morawitz, Elizabeth; Shin, Haejung; Funk, Michelle
One of the most potent ways to communicate stigma is associating a group with peril. In this study, we examine how different forms of peril representations influence specific patterns of interpersonal inclinations. We explore how key social perceptions of group warmth and competence may serve as explanatory mediating mechanisms. Although African Americans and Arab-Muslims similarly share close mediated associations with threat, an empirical examination of how interaction intentions toward both groups differ under congruent conditions is warranted. Results demonstrate support for expectations pertaining to Arab-Muslims, though not African Americans, revealing the complicated nature of threat-influenced antipathy toward these groups.